Analyzing Sick Building Syndrome in Architecture Studios of EMU - Soleimanipirmorad, Soheil (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Sick building syndrome (SBS) is one of the important issues of our contemporary age where people are facing problems derived from buildings, and this issue is becoming an important concern especially in modern life due to its heavy consequences. SBS includes various general symptoms that affect the users of a building. The SBS effect can be seen on individuals as a group of symptoms which appear specifically at working places. Some of the common symptoms are headache; loss of concentration, runny nose, itching, dry skin and dry eyes. The most important characteristic of SBS is such that it is not always easy to recognize the problem and the lack of awareness amongst designers and users about SBS causes other problems like reducing of the productivity of the employees in a working place or learning capacity of students in an educational building. Recognizing and finding proper solutions for problems in sick buildings will help create healthy environments and lead to more productiveness at work, therefore it is important to be aware of the subject and take it serious specially at this modern era where these issues matters a lot. In this research, signs of SBS will be observed and analyzed in the Architectural Studios of EMU (A18, A27) as the case study of research because it is very important for an educational building to provide a healthy environment that students can perform better and have the maximum productivity. The methodology of research is a mix of qualitative and quantitative approach to collect required data. The aim is to find out if the users of studios are suffering from sick building syndrome effects and propose some possible solutions for their improvement. For this purpose, the named lecture/studio rooms of interior architecture have been analyzed with observations and questionnaires where possible factors leading to SBS has been pinned.. After collection of sufficient data and their analysis, the results showed that the building is suffering from SBS impacts; students were effected by some of SBS syndromes and it affected their performance and health conditions. Keywords: Educational Building, SBS, Health, User, EMU

ÖZ: Hasta bina sendromu, insanların bundan kaynaklanan problemlerle karşı karşıya kaldığı çok önemli bir konudur ve bu konu, özellikle modern yaşamda, sonuçlarının ağır olabileceği önemli bir sorun haline gelmektedir. Hasta bina sendromu, bir binadaki kullanıcılarda meydana gelen farklı genel belirtileri içerir. SBS etkisi, bireylerde özellikle çalışma yerlerinde görülen bir semptom grubu olarak tanımlanabilir. Sık görülen semptomlardan bazıları baş ağrısı; konsantrasyon kaybı, burun akıntısı, kaşıntı, kuru cilt ve gözlerde kuruluktur. Bu konuda yaşanan en önemli sıkıntılarından bazıları, çalışanların işyerindeki üretkenliklerinin azalması ve öğrencilerin eğitim binalarındaki öğrenme kapasitelerinin azalması gibi sorunların ortaya çıkmasıdır. Ancak kullanıcıların bu problemi tanıyabilecek kadar yeterli farkındalıklarının olması her zaman karşılaşılan bir durum değildir. Hasta binalardakı problemlere uygun çözümleri tanımak ve bulmak, kullanıcılara sağlıklı bir ortam oluşturacak ve kullanıcıların üretkenliğini artıracağı için, bu konuları farkında olmak ve özel önem vermek önemlidir. Bu araştırmada, SBS belirtileri, bir eğitim binası öğrencilerine sağlıklı bir ortam sağlamak için çok önemli olduğundan, DAÜ Mimarlık Stüdyoları (A18, A27) araştırmanın örnek çalışması olarak gözlemlenecek ve analiz edilecektir. Araştırma metodolojisi, gerekli verilerin toplanmasında niteliksel ve niceliksel yaklaşımlardan yararlanmıştır. Amaç, stüdyo kullanıcılarının hasta bina sendromu etkilerinden olumsuz etkilenip etkilenmediklerini anlamak üzere binaları analiz etmek olası faktörleri göz önünde bulundurarak bazı çözümler önermek ve aynı zamanda anketler aracılığı ile bina içinde iken kullanıcıların durumunu gözlemlemektir. Yeterli veri topladıktan ve analiz ettikten sonra sonuçlar seçilen mekanlarda hasta bina sendromu etkisinin olduğunu göstermiştir. Öğrenciler SBS sendromunun bazılarından etkilenmiş ve bu durum performanslarını ve sağlık durumlarını da etkilemiştir. Anahtar Kelimeler: Eğitim Binası, HBS, Sağlık, Kullanıcı, DAÜ
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2018. Supervisor: Assoc. Prof. Dr. Sadiye Müjdem Vural.
Keywords: Sick Buildings--Environmentally induced diseases--Environmental Illness; Sick building syndrome--Architecture Studios--Eastern Mediterranean University; Sick building syndrome--Indoor air pollution - Health aspects; Buildings--Health aspects; Educational Building; SBS; Health; User; EMU; Architecture